Dynamic factors and electromyographic activity in a sprint start - Coh, M.; Peharec, S.; Bacic, P.; Kampmiller, T. (Biology of Sport, 2009)
The aim of the study was to establish the major dynamic parameters as well as the EMG activation of muscles in a sprint start as the first derivative of sprint velocity. The subject of the analysis was block velocity, the production of force in the front and rear starting blocks, the block acceleration in the first two steps and the electromyographic activity (EMG) of the following muscles: the erector spinae muscle, gluteus maximus muscle, rectus femoris muscle, vastus medialis muscle, vastus lateralis muscle, biceps femoris muscle and gastrocnemius-medialis muscle. One international-class female sprinter participated in the experiment. She performed eight starts in constant laboratory conditions. The 3-D kinematic analysis was made using a system of nine Smart-e 600 cameras operating at a frame rate of 60 Hz. Dynamic parameters were established by means of two separate force platforms to which the starting blocks were fixed. A 16-channel electromyograph was used to analyse electromyographic activity (EMG). It was established that the block velocity depended on the absolute force produced in the front and rear starting blocks and that it was 2.84±0.21 m.s-1. The maximal force on the rear and front blocks was 628±34 N and 1023±30 N, respectively. In view of the total impulse (210±11 Ns) the force production/time ratio in the rear and front blocks was 34%:66%. The erector spinae muscle, vastus lateralis muscle and gastrocnemius-medialis muscle generate the efficiency of the start. The block acceleration in the first two steps primarily depends on the activation of the gluteus maximus muscle, rectus femoris muscle, biceps femoris muscle and gastrocnemius-medialis muscle. A sprint start is a complex motor stereotype requiring a high degree of integration of the processes of central movement regulation and an optimal level of biomotor abilities.